2020
DOI: 10.3390/atmos11020175
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Westerly and Easterly Quasi-Biennial Oscillation Phases on the Connection between the Madden–Julian Oscillation and the Arctic Oscillation

Abstract: Previous studies have revealed the relationship between the Madden-Julian oscillation (MJO) and the Arctic Oscillation (AO). The MJO phase 2/3 is followed by the positive AO phase, and the MJO phase 6/7 is followed by the negative AO phase. This study reveals that the MJO phase 6/7-AO connection is modulated by the Quasi-Biennial Oscillation (QBO) through both tropospheric and stratospheric pathways during boreal winter. The MJO 2/3 phase and AO relationship is favored in both QBO easterly (QBOE) and westerly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Perhaps most striking is the enhanced MJO impact and increased prediction skill following active MJO events during WQBO over the North Atlantic in weeks 3-4 in both ECMWF and NCEP. This result is supported by recent research showing that the North Atlantic Oscillation and MJO connection is stronger during WQBO (Feng and Lin, 2019;Song and Wu, 2020). Furthermore, enhanced prediction skill of atmospheric rivers over Alaska is also found following active MJOs during WQBO (Baggett et al, 2017).…”
Section: Regional Prediction Skillsupporting
confidence: 82%
See 2 more Smart Citations
“…Perhaps most striking is the enhanced MJO impact and increased prediction skill following active MJO events during WQBO over the North Atlantic in weeks 3-4 in both ECMWF and NCEP. This result is supported by recent research showing that the North Atlantic Oscillation and MJO connection is stronger during WQBO (Feng and Lin, 2019;Song and Wu, 2020). Furthermore, enhanced prediction skill of atmospheric rivers over Alaska is also found following active MJOs during WQBO (Baggett et al, 2017).…”
Section: Regional Prediction Skillsupporting
confidence: 82%
“…This result is supported by a growing body of work suggesting the importance of WQBO on MJO teleconnections. For example, recent work has shown that the North Atlantic Oscillation and MJO relationship are stronger during WQBO (Feng and Lin, 2019;Song and Wu, 2020), and prediction skill of atmospheric rivers over Alaska is enhanced following WQBO-MJO (Baggett et al, 2017). Finally, while strong ENSO events were removed from our analysis in an attempt to separate the effects of the QBO from those of ENSO, an ENSO influence may still remain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weakening of stratospheric polar vortex related to SSW events could also affect upper levels up to the ionosphere including its chemical composition (Funke et al, 2017;Pedatella et al, 2018). Meanwhile, the Arctic stratosphere acts as a pathway linking the extratropical surface climate to tropical El Niño-Southern Oscillation (ENSO) (e.g., Butler et al, 2014;Cagnazzo and Manzini, 2009;Domeisen et al, 2019;Fletcher and Cassou, 2015;Hurwitz et al, 2014;Ineson and Scaife, 2009;Toniazzo and Scaife, 2006;Zhou et al, 2020), Madden-Julian oscillation (MJO) ( Barnes et al, 2019;Song and Wu, 2020), Arctic sea ice change (e.g., De and Wu, 2019;Hell et al, 2020;Kim and Son, 2020;Overland and Wang, 2019), and Indian Ocean dipole (IOD) (Hardiman et al, 2020). However, not every Arctic stratospheric polar vortex strengthening or weakening event affects the troposphere, whose state can also play an important role (Domeisen et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…However, the study of Garfinkel and Hartmann (2010) showed that the QBO modifies the teleconnections between the tropics and extratropics through both direct and indirect (background flow related) processes. Subsequent studies examined the influence of the QBO on the MJO-NAO teleconnection (Feng & Lin, 2019;Song & Wu, 2020). During extended winters, from November to April, after the occurrence of MJO phases 3 and 7, the NAO in both phases was found to have a larger amplitude in WQBO years than in EQBO years (Feng & Lin, 2019).…”
Section: Introductionmentioning
confidence: 99%